HUBUNGAN ASUPAN ENERGI DAN PROTEIN, RIWAYAT PENYAKIT INFEKSI DAN PICKY EATING DENGAN KEJADIAN STUNTING DI KECAMATAN CISAYONG KABUPATEN TASIKMALAYA - Rohmania, Diah; Lina, Nur; Novianti, Siti (Jurnal Kesehatan Komunitas Indonesia, 2024)
Stunting ranks first for nutritional problems for 3 consecutive years starting from 2019, 2021 to 2022. Based on the SSGI, the prevalence of stunting in West Java is 20.2%. Tasikmalaya Regency is included in the 5 regencies/cities with a relatively high stunting incidence rate of 27.2% with several sub-districts being the locus, one of which is Cisayong District which has a stunting prevalence of 20.48%. The purpose of this study was to determine the relationship between energy and protein intake, history of infectious diseases and picky eating with the incidence of stunting in Cisayong District, Tasikmalaya Regency. The independent variables studied were energy intake, protein intake, history of infectious diseases, and picky eating. This research is an observational study with a case control design. Sampling in the case group used a proportionate stratified random sampling technique and in the control group used a purposive sampling technique with a ratio of 1:2. The bivariate test in this study used the chisquare test analysis. The results showed that there was a relationship between energy intake and the incidence of stunting with a p-value = 0.000 and OR = 9.892, there was a relationship between protein intake and the incidence of stunting with a p-value = 0.000 and OR = 4.372, there was a relationship between a history of infectious diseases with the incidence of stunting with a p-value = 0.009 and OR = 2.729 and there is also a relationship between a history of infectious diseases and stunting with a p-value = 0.002 and OR = 3.242.